MAJELIS TAKLIM AND ITS ROLE IN WOMEN'S EMPOWERMENT - Ridho, Muhammad Ali; Putra, Andi Eka; Jamil, Muhammad (Universitas Islam Negeri Raden Intan Lampung, 2023)
This research describes the activities of Majelis Taklim Rachmat Hidayat in empowering women in Bandar Lampung city. Majlis Taklim in the current era is not just a base for the transformation of religious knowledge. But it also carries out the function of social exchange, including through women's empowerment. The focus of this research is How is the role of the Rachmat Hidayat Taklim assembly in empowering women in Bandar Lampung city? The research concluded that Rachmat Hidayat's Majelis Taklim has succeeded in encouraging women's participation in religious, economic, and social fields. Majelis Taklim Rachmat Hidayat has become a transformative forum for the women's movement in the city of Bandar Lampung